Introduction Of Information Technologies Knowledge Control From Economical Disciplines - Kobets, V.M. (Journal of Information Technologies in Education (ITE), 2009)
In article basic aspects introduction integrated environment verification knowledge students from economic disciplines are ehpounded. It is resulted list modules given environment and classification assignments in relation to control knowledge students from normative economical disciplines. It is noted advantages arplication information technologies at different types current and final control knowledge students different forms teaching.